Anti-inflammatory and antimicrobial activities of hippocratea indica root bark and poga oleosa fruits (2007)
The methanolic extracts of Hippocratea indica root bark and Poga oleosa fruits were investigated for anti-inflammatory and antimicrobial activities. Both extracts inhibited carrageenan-induced paw oedema significantly in rats in a dose-dependent manner in 4 h. H. indica inhibited oedema significantly at the minimal dose (125 mg/ml, p< 0.05) from 2 h onward, and gave 100% inhibition in 4 h. at 250 mg/kg. It was shown to be a more potent anti-inflammatory agent than P. oleosa. Also, H. indica extract exhibited greater antimicrobial activity against tested bacteria, with Staphylococcus aureus being the most susceptible bacterium (MIC, 16 mg/ml). Both plants were inactive against Candida albicans. These results confirm the anti-inflammatory and antibacterial activities of the two plants.